Evaluation model for multi‐microgrid with autonomous DC energy exchange. Issue 5 (19th May 2017) - Werth, Annette; Kitamura, Nobuyuki; Tokoro, Mario; Tanaka, Kenji
Abstract : This paper proposes an evaluation model to analyze the impact of microgrid topologies on self‐sufficiency for a given size of batteries and photovoltaic (PV) panels (resources). Three topologies are evaluated for a community of 19 houses: centralized resources (ideal case), stand‐alone resources, and a multi‐microgrid topology with autonomous exchange. Depending on the ratio of PV and battery size, the topology with stand‐alone resources has a clear disadvantage in terms of self‐sufficiency compared to the centralized, ideal topology. To counteract this, we propose a hybrid topology: households are interconnected so that they can exchange energy between each other based on an autonomous energy exchange algorithm we developed. We show that for a well‐chosen ratio of batteries and PV, the interconnected system can improve the stand‐alone design by up to 10% without requiring any additional resources. This topology can approach performance similar to that of a centralized microgrid but its design is more flexible and resilient to failures or accidents. The evaluation model computes the self‐sufficiency ratio (SSR) for the three topologies for 0–20 kWh batteries and 1–14 kWp PV sizes. Furthermore, seasonal differences in SSR per topology are analyzed for an actual community with real resources. We also calculate the savings in PV and battery due to the interconnected topology. Finally, the third topology's feasibility is demonstrated on a full‐scale platform in Okinawa on which the autonomous energy exchange software was tested for over a year in a community of 19 houses. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.